Inuit Symbolism of the Bearded Seal - Sonne, Birgitte (Études Inuit Studies, 2017)
The skins of the bearded seal—both dress and interior skins—were indispensable in Inuit/Yupiit technology. Converted into straps, thongs, covers, pokes, rain clothing, and underwear, the skins served to make transport possible, facilitate hunting activities, and protect people against wet and stormy weather. Similarly, the same skin objects permitted contact and exchanges with the beings of the Other Worlds, on which the earthly life of humans depended. Symbolic analysis of the characteristics of bearded seal as reflected in ritual, myth, and sayings reveals that bearded seal turns out to bear both frightening and beneficial meanings. Feared in the figure of a bogey at the height of winter, welcomed as the first seal to arrive from a great distance in early spring, inspiring reproduction and protecting Raven in renewing the earth at equinoxes, bearded seal made the Inuit/Yupiit world cohere.